“Loué soit le très-saint Sacrement” – Monastic Life in the Eighteenth-century Benedictine Monastery in Warsaw in Light of the Correspondence of Maria Augustyna Radziwiłł - Penkała-Jastrzębska, Anna (History / Istorija, 2025)
The study presented here deals with the peculiarities of the functioning of the order The Benedictine Nuns of Perpetual Adoration of the Blessed Sacrament in the 18th century. The Sacramental Nuns led a simple, modest life based on a constant rhythm of adoration. Their rule was based on essentially the same principle as that of other Benedictine orders. In view of the fact that most of the historical sources concerning the functioning of the congregation in the 18th century have been destroyed, of particular importance is the found private correspondence of one of the prioress of the order – Maria Augustyna Radziwiłł. Her correspondence (found in The Central Archives of Historical Records in Warsaw) has not previously been analysed by researchers, hence its potential for use in recognising the presented issue is enormous. The aim of the research was to determine what daily life was like in the order during the times of King August III Wettin and Stanislaw August Poniatowski. Of particular importance is the analysis of the economic condition of the monastery, relations with benefactors, the standard of living of the nuns and the implementation of the foundation act. The presented findings are part of a broader current of research on monastic life in the Polish-Lithuanian Commonwealth in the 18th century.